implementasi deteksi risiko tinggi kehamilan berbasis GEBRAK (Gerakan Bersama Amankan kehamilan) di bojonegoro - Nur Azizah (Jurnal Ilmiah Bidan (JIB), 2020)
GEBRAK is joint together save pregnancy and assistance high risk pregnant women reduction efforts ibu mortality and neonatal undertaken in kabupaten bojonegoro education health by involving institutions.The research aims to explain the implementation of detection high risks pregnancy some as: input . process of, and output GEBRAK Program, Bojonegoro health department educational institutions and Comunity Health Center (Puskesmas).Research method is a qualitative approach and the design of descriptive phenomenology , with informants main person in charge of the program gebrak health agency and educational institutions , as well as supporting the midwife Coordinator informants , the midwife , and pregnant mothers gebrak participants is drawn in through the sampling method of purposive .Data was gathered through in-depth interviews and study documentation. The research results five sources core has been participating in this research.The interview was filmed later made. interview transcriptsThe research results indicate that in the aspect of the input that bojonegoro district health department does not have technical implementation guidelines kick some ass, program on the process of the program with assistance to kick some ass do with since i was pregnant until with 42 days after giving birth to record all findings and report immediately to puskesmas, if there were complications while on the aspect of the output of recording and reporting have not specifically conducted using special formatting, the report carried on a routine report puskesmas.Conclusion bojonegoro health department bojonegoro district do not have a specific guidebook as a guide and technical guidelines , but as preparation the socialization and cooperation with educational institutions that appointed to partnered .Denngan program gebrak can be detected complication in a premature manner for pregnant women who was accompanied by , however, the program is felt to be less effective because not all pregnant women get assistance given the amount of students obstetrics who do not reach pregnant women which is more , so we needed health program other lingkupnya broader and involving another profession and cross-sectors to to reach out to all pregnant women